OMTI All-Sky Imager Quick-Look Data (OI emission 732.0 nm, 30 sec) at Tromso, Norway. - Kazuo Shiokawa; Yuichi Otsuka; ISEE IUGONET Metadata Management Group (名古屋大学, 2022)
Optical Mesosphere Thermosphere Imagers (OMTI) All-Sky Imager Quick-Look Data of OI emission taken with the 777.4nm filter at Tromso, Norway. dataset